NEW PATTERNS OF STRAIN ON THE HEALTH OF BANK WORKERS: A GEOGRAPHICAL ANALYSIS OF THE COST OF PRODUCTIVITY - Oliveira, Matheus Buttler de [UNESP]; Heck, Fernando Mendonca (Univ Estadual Paulista Julio Mesquita Filho, Fac Ciencias & Tecnologia, 2024)
This article proposes an in-depth investigation into the implications of productive transformations in the banking sector and their direct effect on workers' health. By exploring changes in the work environment, we examine how these transformations influence worker health, pointing to new patterns of strain, especially related to work-related mental disorders. Using a Marxist approach, through an interdisciplinary literature review and the analysis of statistical data on employment in the banking sector and sick leave, we examine the relationship between increasing productivity demands and the challenges faced by professionals in the industry. The results highlight not only the correlation between changes in the work environment and the rise in illness cases but also a managerial strategy by employers to handle human suffering.
Keywords: Productive Restructuring; Banking Work; Worker Health